Long-term Survival of Patients With Invasive Ultra-thin Cutaneous Melanoma: A Single-center Retrospective Analysis. Issue 2 (January 2016) - Vecchiato, Antonella; Zonta, Elisa; Campana, Luca; Dal Bello, Giacomo; Rastrelli, Marco; Rossi, Carlo Riccardo; Alaibac, Mauro
Abstract : Abstract: The incidence of cutaneous melanoma is increasing worldwide, especially for thin melanoma (Breslow ⩽1 mm). Thin cutaneous melanoma has a favorable prognosis but there are few data about the prognosis of patients with ultra-thin cutaneous melanoma (Breslow ⩽ 0.5 mm). Our aim was to investigate the disease-free survival among patients with invasive cutaneous melanoma with Breslow ⩽ 0.5 mm after 10 years from the initial diagnosis. A retrospective review of 240 cutaneous melanoma patients with Breslow ⩽ 0.5 mm was performed. Recurrence, death from cutaneous melanoma, and disease-free survival were all identified. In the whole group of patients, we observed only 2 deaths from cutaneous melanoma. Median follow-up was 13, 11 years. Among all 240 patients, 221 were alive and disease free, 2 died of cutaneous melanoma, 11 died of other non-neoplastic diseases, 5 died of other neoplastic diseases different from melanoma, and 1 patient had a local recurrence; therefore the 10-year melanoma survival rate was 99.6%. Our data indicate that death from cutaneous melanoma in the group of patients with Breslow ⩽0.5 mm was a very rare event and that diagnosis at this stage dramatically decreases the risk of developing metastatic tumors to a <0.5% also after a 10-year period of follow-up. Limitation of the study includes the fact that other risk factors for melanoma, notably ulceration, and mitotic rate, were not evaluated.